2017
DOI: 10.30707/jste52.1nite
|View full text |Cite
|
Sign up to set email alerts
|

Explicating the Characteristics of STEM Teaching and Learning: A Metasynthesis

Abstract: This metasynthesis focused on STEM teaching and learning practices in middle and high school classrooms and in informal settings. Research artifacts between 2005 and 2012 were examined. Fifty-eight unique artifacts were classified into four categories: reform-based teaching and learning, informal education, teacher factors, and technology use. Promising pedagogical reform-based practices included inquiry-based learning, engineering design, project-based learning, problem-based learning, and hands-on practices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The design tasks required students to make recommendations for design decisions supported by background information, content, and data from prototypes. The study findings support prior literature that signifies the inclusion of the intentional integration of STEM disciplines in well‐designed curriculum materials helps enhance students' understanding of science concepts (e.g., Furner & Kumar, 2007; Guzey et al, 2016; Nite et al, 2017; Wendell & Rogers, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The design tasks required students to make recommendations for design decisions supported by background information, content, and data from prototypes. The study findings support prior literature that signifies the inclusion of the intentional integration of STEM disciplines in well‐designed curriculum materials helps enhance students' understanding of science concepts (e.g., Furner & Kumar, 2007; Guzey et al, 2016; Nite et al, 2017; Wendell & Rogers, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Studies suggest that these experiences will allow the students to make decisions about their career paths and develop STEM identities during middle school years (Beier et al, 2019; English & King, 2019; Ganesh & Schnittka, 2014; Guzey et al, 2016, 2017; Maltese & Tai, 2010). Other benefits of STEM integration include having students engage in hands‐on and authentic experiences by providing students a real‐life context‐based academic learning and problem‐solving skills (Cunningham et al, 2020; Dailey et al, 2018; Guzey et al, 2017; Hernandez et al, 2014), enhancing higher‐level thinking skills (Capraro & Slough, 2013; Kelley & Knowles, 2016), improving conceptual understanding and academic performance (Nite et al, 2017; NAE/NRC, 2014.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common finding in the individual studies that, apart from motivation, STEM education enables students to develop positive attitudes, gives responsibility, increases self-confidence, and raises awareness of both real-life problems and themselves. In support for these findings, Yildirim (2016) and Nite et al (2017) found in their meta-synthesis studies that STEM education contributes to the development of students' positive attitudes toward STEM domains. The fact that students develop positive attitudes toward STEM domains can also support their future careers in STEM fields (Koszalka, Wu & Davidson, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…There are also meta-synthesis studies in the literature that determine the characteristics of STEM education (Nite, Capraro, Capraro & Bicer, 2017) and the effect of STEM education on academic success, skills, and attitude (Yıldırım, 2016). In the metasynthesis study conducted by Nite et al (2017), 57 individual studies were categorized in terms of their characteristics as reform-based learning and teaching, informal education, teacher factors and technology use. Reform-based applications cover the inquiry-based instruction, engineering design, project-based instruction, problem-based instruction, and applied activities.…”
Section: Introductionmentioning
confidence: 99%